2020
DOI: 10.31557/apjcc.2020.5.2.71-78
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Primary Tumours, How Frequent we can Offer Curative Therapy?

Abstract: Background: Patients with Multiple-primary Malignancies are usually excluded from clinical trials. Clinical information re-distribution, associations, response to treatment and prognosis are scared. Collecting information will help us to expect the impact of prior therapies and to teach us how to best treat them. This study aims to report cases in our society and to see if we have a special predilection of certain Multiple-primary Malignancies in our region based on different geographic and environmental risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…Clinical studies have suggested that the possible molecular mechanisms of drug resistance in gliomas include mutations in the targets of genes acting under chemotherapeutic agents and diminished apoptosis of tumor cells. Mutations in key genes along these signaling pathways can lead to drug resistance in tumor cells (17,24,25) (Fig. 2).…”
Section: Drug Resistance Analysismentioning
confidence: 99%
“…Clinical studies have suggested that the possible molecular mechanisms of drug resistance in gliomas include mutations in the targets of genes acting under chemotherapeutic agents and diminished apoptosis of tumor cells. Mutations in key genes along these signaling pathways can lead to drug resistance in tumor cells (17,24,25) (Fig. 2).…”
Section: Drug Resistance Analysismentioning
confidence: 99%
“…Dựa trên các tiêu chí được đề xuất bởi Warren và Gates, chẩn đoán nhiều ung thư nguyên phát trên cùng một bệnh nhân bao gồm những đặc điểm sau [3][4][5][6] : (i) Tổn thương ác tính của từng loại khối u phải được xác định bằng mô bệnh học; (ii) Mỗi loại u ác tính xảy ra ở các vùng hoặc cơ quan khác nhau; (iii) phải loại trừ khả năng mắc bệnh ung thư ác tính thứ hai là di căn của bệnh ung thư ác tính thứ nhất. Hiện nay, với các tiến bộ trong chẩn đoán và điều trị ung thư đã làm cải thiện đáng kể thời gian sống thêm của từng bệnh lý ung thư cơ quan nhưng vấn đề tiếp cận chẩn đoán cũng như điều trị vẫn còn là một thách thức trong y học 2,5,7,8 . Tại bệnh viện hữu nghị Việt Đức, chúng tôi đã phẫu thuật điều trị ung thư trực tràng và ung thư phổi cho một bệnh nhân nam 71 tuổi được thực hiện bởi các chuyên ngành chuyên sâu khác nhau, đem lại kết quả tốt sau phẫu thuật.…”
Section: đặT Vấn đềunclassified
“…Điều trị ung thư là điều trị đa mô thức (phối hợp giữa phẫu thuật, xạ trị, hóa trị, điều trị đích, liệu pháp miễn dịch…). Tùy thuộc vào kết quả mô bệnh học, giai đoạn bệnh và thể trạng bệnh nhân mà có lựa chọn các chiến lược và phác đồ điều trị tương ứng phù hợp nhất cho người bệnh 7,8 . Do đó, đối với bệnh nhân ung thư, việc chẩn đoán xác định bệnh và giai đoạn bệnh là một yếu tố quyết định chính đến phương thức điều trị cho bệnh nhân góp phần làm tăng khả năng sống sót và tuổi thọ của bệnh nhân 2,3,5 .…”
Section: Bàn Luậnunclassified
“…Endometrial cancer, as one of the most common tumors in the female reproductive system, is only secondary to cervical cancer in prevalence. A survey in recent years has shown an increasing trend of the mortality rate and morbidity rate in the world, gradually affecting the health of the younger women (5,16). Correspondingly, the application of tumor markers has facilitated the progress of cancer surveys, screening of the high-risk population, differential diagnosis, and evaluation of clinical stage of tumor, efficacy and prognosis of treatment (17,18).…”
Section: Comparison Of the Follow-up Of Patients Between Two Groupsmentioning
confidence: 99%
“…Recently, people have increasingly noted the significance of post-surgery chemotherapy, synchronized chemotherapy and radiotherapy or a combination of them in the treatment of various cancers, while the efficacy and tolerance remain uncertain (4). According to the current guidelines for the diagnosis and treatment of endometrial cancer, auxiliary radiotherapy is not necessary for patients with low-risk endometrial cancer, or with only one high-risk factor, while for moderate-risk endometrial cancer, guided brachytherapy is more preferred than external irradiation and for high-risk endometrial cancer, and chemotherapy may work better in improving the median survival time (5)(6)(7). Pelvic external radiation is the major auxiliary method for treatment of endometrial cancer patients with high-risk pathogens, while so far, intensity-modulated radiation therapy (IMRT) is extensively applied in the treatment of prostatic cancer and head and neck tumors, gaining promising efficacy, while leaving no damage to the adjacent normal tissues (8).…”
Section: Introductionmentioning
confidence: 99%